1982
DOI: 10.1017/cbo9780511629198
|View full text |Cite
|
Sign up to set email alerts
|

Coding the Universe

Abstract: Axiomatic set theory is the concern of this book. More particularly, the authors prove results about the coding of models M, of Zermelo-Fraenkel set theory together with the Generalized Continuum Hypothesis by using a class 'forcing' construction. By this method they extend M to another model L[a] with the same properties. L[a] is Gödels universe of 'constructible' sets L, together with a set of integers a which code all the cardinality and cofinality structure of M. Some applications are also considered. Grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 0 publications
0
83
0
Order By: Relevance
“…This is achieved (for a somewhat smaller class of cardinals κ) in the next theorem. 3 Remember that, given an uncountable cardinal κ, a subset S of κ is fat stationary if for every club C ⊆ κ, the intersection C ∩ S contains closed subsets of ordinals of arbitrarily large order-types below κ. Given regular cardinals η < κ, we let S κ η denote the set of all limit ordinals less than κ of cofinality η.…”
Section: (I) Every Subset Of ω Is An Element Of L[z]mentioning
confidence: 99%
See 1 more Smart Citation
“…This is achieved (for a somewhat smaller class of cardinals κ) in the next theorem. 3 Remember that, given an uncountable cardinal κ, a subset S of κ is fat stationary if for every club C ⊆ κ, the intersection C ∩ S contains closed subsets of ordinals of arbitrarily large order-types below κ. Given regular cardinals η < κ, we let S κ η denote the set of all limit ordinals less than κ of cofinality η.…”
Section: (I) Every Subset Of ω Is An Element Of L[z]mentioning
confidence: 99%
“…In this section, we discuss almost disjoint coding forcing (see [3] and [12]) for uncountable cardinals κ that satisfy κ = κ <κ . Given such κ, this forcing technique will allow us to make an arbitrary subset of κ κ definable by a formula of low complexity in an upwards-absolute way.…”
Section: Almost Disjoint Coding At Uncountable Cardinalsmentioning
confidence: 99%
“…We then let P 4 consist of all pairs p = (l(p), r(p)), where l(p): n → 2 for some n < ω and r(p) is a finite subset of ω 1 …”
Section: Coding Below One Strong Cardinalmentioning
confidence: 99%
“…These result use either reverse Easton or forward Easton forcing methods. An example of the latter is due to Jensen [1], who showed that in L[0 # ] there is a real which is class-generic but not set-generic over L. All of these early results however only produce models of GCH.…”
Section: Introductionmentioning
confidence: 99%